The Impact of Digital Communication Technologies on Indigenous Language Preservation and Revitalization in Nigeria: A Conceptual Exploration - MBEY, Etete Gregory; ITAM, Komomo Okoi; EKI, Margaret Vincent (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The rapid advancement of digital communication technologies presents both challenges and opportunities for the preservation and revitalization of indigenous languages in Nigeria. With over 500 languages at risk of extinction due to globalization, urbanization, and the dominance of English and Nigerian Pidgin, digital tools such as social media, artificial intelligence (AI), mobile applications, and online learning platforms offer innovative pathways for linguistic sustainability. This non-empirical study explores the conceptual frameworks surrounding digital language preservation, analyzing how technology can be harnessed to document, promote, and revitalize Nigeria’s indigenous languages. Key considerations include the role of digital media in fostering intergenerational language transmission, the effectiveness of AI-driven language tools, and the policy interventions needed to support digital linguistic initiatives. By engaging with sociolinguistic theories, digital humanities, and decolonial perspectives, this paper contributes to the discourse on language sustainability in the digital age, offering recommendations for policymakers, educators, and technology developers.